Acetabular ventroversion using the sacroiliac wedge, with or without pelvic osteotomies in dogs: An ex vivo study - Ikenaga, Fernanda M.; Rocha, Jessé R.; Carvalho, Leonardo L.; Honsho, Cristiane S.; Dias, Fernanda G.G.; Costa, Rodrigo C. [UNESP]; Rocha, Thiago A.S.S. [UNESP]; Dias, Luís G.G.G. [UNESP] (FapUNIFESP (SciELO), 2019)
Canine hip dysplasia (CHD) is a common condition observed in the surgical clinics for small animals. Among the surgical techniques for management of CHD, triple pelvic osteotomy and sacroiliac wedge promote acetabular lateral axial rotation (ventroversion), increasing acetabular coverage and joint stability. The present study aimed to evaluate radiographically, by measuring the Norberg angle (NA) and the acetabular coverage percentage (ACP), the acetabular ventroversion induced by the sacroiliac wedge technique, with or without pelvic osteotomies; we also checked the feasibility of wedges made of polyamide with an angulation of 20° and 30°. The software used to measure NA and ACP was AutoCAD 2009. Pelves from 10 canine corpses were evaluated radiographically at four time-points: M0 (Control Group), M1 (wedges of 20° and 30°), M2 and M3 (wedges associated with bilateral pubis and ischium osteotomies, respectively). There was no significant increase in the acetabular ventroversion at M1, M2, and M3. The polyamide sacroiliac wedge technique proved to be feasible, stable, and easy to apply. Further, the software proved to be efficient and easy to use for NA and ACP measurements. In the present study, even in the cases of non-dysplasic adult canine corpses, it was concluded that the sacroiliac wedge technique does not require to be accompanied by pubis and ischial osteotomies because they did not significantly increase the NA and ACP.
Keywords: Acetabular ventroversion; Canine hip dysplasia; Clinics; Dogs; Ex vivo; Pelvic osteotomies; Sacroiliac wedge; Surgery